Creative criteria to develop product design in life skills classroom - Rosli, D’oria Islamiah; Nong Chik, Syarina Azura (IEEE Xplore, 2018)
In the era of 21 st century, creative students are the national asset that can contribute to the development of society, nation and economic growth. Applying creative criteria in life skills subject, help in preparing students with skilled workforce, professionals, entrepreneurs and product designers that in line with the demand of the current technology. There is a gap where students try to copy or replicate the product design available around them, and these restricted them to think creatively in producing innovative product design. Therefore this study is to investigate problems faced by students in developing product design in life skills subject and secondly is to investigate how the process of developing the product design will contribute to student's creativity in producing a product. To date, this study will employ interview and observation method in order to gather rich input from the participants. In this study, experts who have more than five years of experiences in product design in Vocational Colleges involved for the interview sessions. In addition, the observation sessions also proceeded with students who took the life skills subject by monitoring their design project progress as to identify criteria that contribute to the discrepancy in developing product design in the classroom. At this stage, at about ten participants involved in this study and most of the participants were students from Vocational Colleges. Findings showed that, there were student self factors that restricted the students to be creative in designing a product in life skills subject. In addition by having conducive classroom environment and supported by guidance from the teachers, intensive discussions, active brainstorming sessions, and interactive interactions were among the activities that help students to be creative and eventually nurturing the students to innovate their product design in the classroom.